Derivatives usage by non-financial companies in Malaysia / Roseamilda Mansor, Khalijah Ramli and Marina Ibrahim - Mansor, Roseamilda; Ramli, Khalijah; Ibrahim, Marina (2012)
The purpose of this research is to examine Malaysian non-financial firms' use of derivatives. In addition, this study contributes to the increased knowledge about a firm's derivatives practices and the impact from factors such as the firm size, category of industry and nationality using these practices. This research has two objectives which are to examine the extent of the derivatives usage in non-financial companies in Malaysia and to determine the key determinant of derivatives usage in non-financial companies in Malaysia. This research involved 286 respondents from non-financial companies, through the use of e-mails. The results of this study show that firms who claimed they are not using derivatives due to their insignificant exposures. It is also found that companies are reluctant to use derivatives due to the disclosures of derivatives activities required under Securities Commission (SC) rules. The study concludes that, the lack of knowledge on derivatives is the major reason for firms not to go against the use of derivatives. This is followed by the inadequate exposure about derivatives.